2000
DOI: 10.1159/000014278
|View full text |Cite
|
Sign up to set email alerts
|

Potential Hazards of Exposure to Di-(2-Ethylhexyl)-Phthalate in Babies

Abstract: Many plastic items are made of polyvinylchloride (PVC) blended with plasticizers. The most frequently used plasticizer is di-(2-ethylhexyl)-phthalate (DEHP). DEHP migrates at a constant rate from plastics to the environment: it has been detected in water, soil and food and is therefore considered as a widespread environmental contaminant. Over the past several years, a number of publications concerning toxic effects of DEHP on animals and humans have been reported. Although DEHP is suggested to be of low acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 66 publications
4
52
1
Order By: Relevance
“…27 In another study, intrauterine DEHP exposure was found to cause a decrease in testis size and testosterone levels. 28 Recently, similar results were reported for human infants. 34 The antiandrogenic effects of DEHP were related to decreased testosterone levels and it is thought that DEHP does not have a direct effect on androgen receptors.…”
Section: Figuresupporting
confidence: 70%
See 2 more Smart Citations
“…27 In another study, intrauterine DEHP exposure was found to cause a decrease in testis size and testosterone levels. 28 Recently, similar results were reported for human infants. 34 The antiandrogenic effects of DEHP were related to decreased testosterone levels and it is thought that DEHP does not have a direct effect on androgen receptors.…”
Section: Figuresupporting
confidence: 70%
“…15,[25][26][27] The toxic effects depend on dose, the age of the person, and the duration of exposure. 28 It has been shown that the toxic effects are much more during infancy, puberty, and pregnancy periods, and long-term small amounts of exposure can cause evident toxic effects. 18 Experimental animal models showed its affects on developmental stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonates in the Neonatal Intensive CareUnit (NICU) environment constitute a population at particularly increased risk. This is of particular relevance, as these newborns may have been likely previously exposed to phthalate esters in utero [18,20] In the present study, various levels of DEHP were detected in all the infusion fluids samples indicating that all pharmaceutical companies use this phthalate ester as a plasticizer in PET container and is leached into the pharmaceutical products. Its average level in different infusion fluids was about 10 ppb.…”
Section: Discussionmentioning
confidence: 51%
“…Hemodialyzed, multiply-transfused, parenterallyfed, extremely-low-birth-weight infants, especially those having severely compromised cardiovascular or renal function, should be considered at greater risk of DEHP toxicity from repeated exposure to the plasticizer over prolonged periods of time. 19 Possible solutions to this dilemma are to use PVC devices that do not contain DEHP (when commercially available), use devices that are made from other materials such as ethylene vinyl acetate, silicone, polyethylene or polyurethane, minimize procedure time to limit DEHP exposure, decrease the storage temperature when DEHP-containing products must be used, and use heparin-coated ECMO circuits. 6,24 Finally, developing an alternative to the currently used blood product storage bag to one that is non-DEHP containing is an identified priority.…”
Section: Discussionmentioning
confidence: 99%